Hounsfield unit value has null effect on thyroid nodules at 18F-FDG PET/CT scans - Filiz Eksi Haydardedeoglu; Gulay Simsek Bagir; Nese Torun; Emrah Kocer; Mehmet Reyhan; Melek Eda Ertorer (Archives of Endocrinology and Metabolism)
ABSTRACT Objectives: Detection rate of thyroid nodules is increasing with the use of new imaging modalities, especially in screening for malignancies. Positron emission tomography/computed tomography (PET/ CT)-positive thyroid nodules should be differentiated for malignancy to avoid unnecessary operations and further follow-up. Most trials evaluate the role of SUVmax, but there is no definitive information about the utility of Hounsfield unit (HU) values for prediction of malignancy. This study aimed to evaluate the HU values beside SUVmax for detecting malignancy risk of PET/CT-positive thyroid nodules. Subjects and methods: Results of 98 cancer patients who had fine needle aspiration biopsy (FNAB) for thyroid nodules detected on PET/CT between January 2011 and December 2015 were assessed. The FNABs and surgical pathological results were recorded. Results: FNABs revealed benign results in 32 patients (32.7%), malignant in 18 (18.4%), non-diagnostic in 20 (20.4%), and indeterminate in 28 (28.5%). Twenty-four patients underwent thyroidectomy. The mean HU values were not significantly different in benign and malignant nodules (p = 0.73). However, the mean SUVmax was significantly higher (p < 0.001) in malignant ones. Area under curve (AUC) was 0.824 for SUVmax; the cut-off value was over 5.55 (p < 0.001), with 80% sensitivity, 84.5% specificity. Conclusions: Our current study demonstrated that HU value does not add any additional valuable information for discriminating between malignant and benign thyroid nodules. We also defined a SUV cut-off value of 5.55 for malignant potential of thyroid nodules detected on PET/CT Arch Endocrinol Metab. 2018;62(4):460-5